One Health approach to vector biology and epidemiology of arboviruses, Rickettsia, and protozoa in smallholder livestock systems in western Kenya - Bastos, Armanda D.S. (University of Pretoria, 2021)
Thesis (PhD (Zoology))--University of Pretoria, 2020.